Cute 'n' creepy crochet : 20+ easy amigurumi patterns for scary creatures, cuddly cryptids, sinister slashers, dangerous dragons and more! - Broderick, Donielle (Media Lab Books/Topix Media Lab, 2025)
"... A fun-filled array of simple amigurumi crochet patterns for creating scarily adorable creatures and characters."--Provided by publisher.